2016
DOI: 10.1159/000445099
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Is One of the Factors Minimizing the Inner Ear Damage from Electrode Insertion in Cochlear Implantation

Abstract: The aim of this study was to investigate the efficacy of preoperative and intraoperative steroid administration for inner ear protection in cochlear implantation (CI). Nineteen subjects who underwent CI were included in the study, and 10 subjects were enrolled as controls (steroid-administered group, n = 19; control group, n = 10). Dexamethasone (dexamethasone sodium phosphate, 5 mg/ml) was systemically administered preoperatively (1 ml) and topically applied during CI (0.5 ml). The extent of hearing preservat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
28
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 49 publications
6
28
0
2
Order By: Relevance
“…The largest decline in hearing occurred within the first month after surgery, a result echoed by a recent study with a cohort having similar thresholds to ours [Cho et al, 2016]. In this study, the early decline was then followed by a more gradual decline.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The largest decline in hearing occurred within the first month after surgery, a result echoed by a recent study with a cohort having similar thresholds to ours [Cho et al, 2016]. In this study, the early decline was then followed by a more gradual decline.…”
Section: Discussionsupporting
confidence: 86%
“…The second was a randomized controlled trial that found topical steroids reduced vestibular symptoms [Enticott et al, 2011]. The third study found a combination of intravenous steroids 1 day and 1 h prior to surgery and then intraoperatively in the RW was shown to have better hearing preservation at 12 months compared to a control group [Cho et al, 2016]. However, this study involved a heterogeneous group with different electrodes, nonrandomization, nonblinding, different insertion techniques, and inconsistent followup between the 2 groups.…”
Section: Introductionmentioning
confidence: 99%
“…Many experimental studies in animals have demonstrated that the use of corticosteroids is able to preserve hearing thresholds, increase the survival of hair cells and spiral ganglia, and decrease the formation of new fibrotic tissue within implanted cochlea (20)(21)(22)(23)(24)(25)(26)(27). Clinical studies demonstrate lower impedances and improved preservation of low-frequency residual hearing in patients when corticosteroids are used in CI surgery (28)(29)(30)(31)(32)(33)(34). The efficacy is attributed to the anti-apoptotic and anti-inflammatory properties of glucocorticoids, by inhibiting immune cells and decreasing the release of inflammatory factors.…”
Section: Introductionmentioning
confidence: 99%
“…Steroids effectively preserve hearing in the basal region (which detects high‐frequency sound) . However, residual hearing in cochlear implantation candidates is largely confined to the apical area (which detects low‐frequency sound) . Drug distribution along the length of the cochlea is determined principally by the rate of drug diffusion relative to that of drug clearance from the scala .…”
Section: Discussionmentioning
confidence: 99%
“…10,24 However, residual hearing in cochlear implantation candidates is largely confined to the apical area (which detects lowfrequency sound). 25,26 Drug distribution along the length of the cochlea is determined principally by the rate of drug diffusion relative to that of drug clearance from the scala. 15 Eastwood et al suggested that the extent of hearing protection in the second turn was greater when a higher steroid concentration was used.…”
Section: Discussionmentioning
confidence: 99%